Pengolahan Citra Digital untuk Menentukan Kadar Asam Askorbat pada Buah dengan Metode Titrasi Iodimetri - Danang Erwanto; Yudo Bismo Utomo; Farrady Alif Fiolana; Mochtar Yahya (MULTITEK INDONESIA, 2018)
Measurement of ascorbic acid in fruits can be implemented by various methods. The method often used to measure ascorbic acid levels is the iodometric titration method. In this research applying digital image processing with color segmentation to measure levels of ascorbic acid using iodimetry titration method, because end point indicator of titration is a change of blue color in the titration solvent. From the research, digital image processing is capable to detect the blue color changes in the titration solvent. Measurement of ascorbic acid level in lime fruit by implementing digital image processing with color space transformation to HSV showed that the average ascorbic acid content was 0.037% and an average error value of 17.54%.